Factors affecting perceived organizational performance with mediation of job satisfaction - Khan Khan Zaman; Haji-Othman Yusuf (Journal of Economics and Management, 2025)
Aim/purpose – The primary intent of the study is to examine the effects of employee empowerment (EE) and employee training (ET) on perceived organizational performance (POP) among the academic and administrative staff of public and private sector higher education institutions of Pakistan with mediation of job satisfaction (JS). Specifically, this study aims to fill the knowledge gap regarding the factors affecting POP in higher education institutions in Pakistan.